Effects of cerebellar transcranial direct current stimulation on rehabilitation of upper limb motor function after stroke - Gong, Qiuwen; Yan, Rubing; Chen, Han; Duan, Xia; Wu, Xiaoyu; Zhang, Xin; Zhou, Yi; Feng, Zhou; Chen, Ya; Liu, Jianbo; Xu, Peng; Qiu, Jing; et al. (Frontiers in Neurology, 2023)
Background: Cerebellum is involved in the control and coordination of movements, while it has still remained unclear whether stimulation of the cerebellum could improve the recovery of upper limb motor function. This study aimed to explore whether cerebellar transcranial direct current stimulation（tDCS）therapy could promote the recovery of upper limb motor function in patients with stroke. Methods: In this randomized, double-blind, sham-controlled prospective study, 77 patients with stroke were recruited and randomly assigned to the tDCS group (n=39) or the control group (n=38). Patients received anodal (2 mA, 20 min) or sham tDCS therapy for 4 weeks. The primary outcome was the change in Fugl-Meyer Assessment-Upper Extremity (FMA-UE) score from baseline to the first day (T1) and 60 days after the stimulation (T2). The secondary outcomes were the FMA-UE response rates assessed at T1 and T2. Adverse events related to the tDCS treatment were also recorded. Results: At T1, the mean FMA-UE score increased 10.7 points (standard error of the mean (SEM) = 1.4) in the tDCS group and 5.8 points (SEM = 1.3) in the control group (difference between two groups was 4.9 points, P = 0.013). At T2, the mean FMA-UE score increased 18.9 points (SEM = 2.1) in the tDCS group and 12.7 points (SEM = 2.1) in the control group (difference between two groups was 6.2 points, P =0.043). At T1, 26 (70.3%) patients in the tDCS group had a clinically meaningful response to the FMA-UE score, and 12 (34.3%) patients in the control group (difference between two groups was 36.0%, P =0.002). At T2, 33 (89.2%) patients in the tDCS group had a clinically meaningful response to the FMA-UE score compared with 19 (54.3%) patients in the control group (difference between two groups was 34.9%, P =0.001). There was no statistically significant difference in the incidence of adverse events between two groups. Conclusion: Cerebellar tDCS can be used as an effective and safe treatment to promote recovery of upper limb motor function in stroke patients.